Design and Development of Efficient Domestic Electric Cum Solar Oven - Aamir Shahzad,; Teyyiba Kanwal ,; Mao-Gang He, (Journal of Basic & Applied Sciences, 2013)
An improved design is proposed to investigate the characteristic study of an electric cum solar oven (ECSO) using circular cover in which both solar energy and electricity have been utilized as energy source for different food items. The newly designed solar oven has been fabricated by employing indigenous raw materials and it provides more reliable performance than the previously used solar oven for cooking of agricultural products and conventional food items. The new observations show that the cooking process of products is dependent on both the circular shape and climate conditions. The electrical heating has been used in combination with the solar energy to enhance the oven heating during the periods of lesser sunshine. The base of the oven was made up of the electric heating plate that is controlled by timer and an electric thermostat is used to control the heating of the oven. The performance and parameters obtained from the newly designed solar oven are found to be excellent than that obtained from previously known solar ovens for cooking of various edibles. It is shown that this newly designed solar oven can be efficient for cooking and preservation of all edible stuffs and appearance of cooked food products. The performance of the solar cooker has been checked under the local climate conditions of Faisalabad city to observe its efficiency with satisfactory results.